Dynamic evaluation of THA components by Prosthesis Impingement Software (PIS) - Giachino, Matteo; Aprato, Alessandro; Revetria, Tullio Andrea; Vezzetti, Enrico; Massè, Alessandro; Ulrich, Luca; Tanzi, Leonardo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the workImplant dislocation in total hip arthroplasties (THA) is a common concern amongst the orthopedic surgeons and represents the most frequent complication after primary implant. Several causes could be responsible for the dislocation, including the malpositioning of the components. Conventional imaging techniques frequently fail to detect the mechanical source of dislocation mainly because they could not reproduce a dynamic evaluation of the components. The purpose of this study was to elaborate a diagnostic tool capable to virtually assess if the range of movement (ROM) of a THA is free from anterior and/or superior mechanical impingement. The ultimate aim is to give the surgeon the possibility to weigh the mechanical contribution in a THA dislocation. MethodsA group of patients who underwent THA revision for acute dislocation was compared to a group of non-dislocating THA. CT scans and a virtual model of each patient was obtained. A software called “Prosthesis Impingement Simulator (PIS)” was developed for simulating the (ROM) of the prosthetic hip. The ROM free of mechanical impingement was compared between the two groups.  Results The PIS test could detect the dislocations with a sensitivity of 71,4%, and a specificity of 85,7%. The Fisher’s exact test showed a p-value of 0,02. The Chi-square test found a p-value of 0,009. ConclusionThe PIS seems to be an effective tool for the determination of hip prosthetic impingement, as the main aid of the software is the exclusion of mechanical causes in the event of a dislocation.